Proses Berpikir Calon Guru Matematika dalam Memecahkan Masalah Geometri Transformasi Berdasarkan Teori John Dewey - Fauzanah, Fauzanah; Nur Malasari, Putri (Institut Agama Islam Negeri Curup, 2024)
Understanding the thinking process of students has great significance, how students face and solve transformation geometry problems not only reflects the understanding of concepts, but also the ability to think systematically, creatively, and logically. The purpose of this study is to find out how the thinking process used by prospective mathematics teachers helps them solve transformation geometry problems. In-depth research on the thinking process of mathematics students in the context of solving transformation geometry problems by utilising John Dewey's theory is expected to provide valuable insights in the development of mathematics education. Descriptive qualitative research method was used in this study. The research subjects were 3 mathematics education students at one of the universities in Kudus Regency. The instruments of this research are mathematical problem solving ability test and interview guidelines. Data analysis method which includes collection, presentation, reduction, and conclusion. The results of the data analysis process based on John Dewey's theory are that the subject is able to understand the problem, define the problem, able to develop a solution if the first solution is not proven, able to test several solutions if there is inaccuracy in the first solution and the subject is able to take the best hypothesis.